Relevansi Isi Buku Teks Pembelajaran PAI dengan Kompetensi Dasar - Cahyanti, Titik Nur (JOEAI (Journal of Education and Instruction), 2021)
This study aims to: 1) To determine the relevance of the contents of the textbook of Islamic Religious Education and Character of Class X SMA Publisher Kemendikbud with KD Permendikbud. 2) To find out the relevance of the content of the textbook of Islamic Religious Education and Character of Class X SMA publisher Erlangga with KD Permendikbud. 3) To find out the relevance of the content of the textbook of Islamic Religious Education and Character of Class X SMA publisher Kemendikbud with the theory of the development of teaching materials. 4) To determine the relevance of the content of the textbook of Islamic Religious Education and Character of Class X SMA Erlangga publisher with the theory of the development of teaching materials. This research is a type of library research or library research. The research began by making a table based on KD Permendikbud and the theory of developing teaching materials. In order to determine the level of relevance in each chapter, the researcher determined five categories of relevance, namely the one that is less, less appropriate, sufficiently appropriate, appropriate, very suitable. Based on the results of research on student textbooks in the subject of Islamic Religious Education class X that the relevance of the criteria for the Islamic Education textbook published by the Ministry of Education and Culture, the 2017 Revised edition based on KD Permendikbud, shows results (very appropriate) and the relevance of the PAI textbook published by Erlangga, the 2019 Revised edition also shows results (very suitable). Meanwhile, the relevance of the criteria for the Islamic Religious Education textbook published by the Ministry of Education and Culture's Revision of 2017 based on the theory of the development of teaching materials, shows results (very appropriate), and the Islamic Education textbook published by Erlangga, the Revised 2019 edition based on the development of teaching materials also shows results (very appropriate). Keywords: Islamic Education Learning, Textbook Relevance, Basic Competencies Curriculum 2013